SPECIES IMPORTANCE IN COASTAL DUNE ECOSYSTEMS IN NORTHERN TURKEY - Ulu Ağır, Ş.; Sürmen, B.; Kutbay, H.G.; İmamoğlu, A. (Annali di Botanica, 2021)
Species importance in coastal dune ecosystems in typical dune zones in Black Sea Region on the north of Turkey was studied by using species conservation index (SCI) approach. SCI scores have significantly differed among dune zones. Additionally, coastal dune species were compared by using seven different criteria (geographic distribution, life span, growth form, conservation status, commonness, the utilitarian and the ecological importance). All of the studied criteria were found to be significant for studied coastal dune species. All of the studied species were moderate to high importance. The highest mean SCI score was found in E zone, while Xanthium strumarium subsp. cavanillesii and Digitaria ischaemum had the lowest SCI scores, and both species occurred in A zone. The highest SCI scores were found in Imperata cylindrica, Eleagnus rhamnoides and Jurinea kilea. The highest Site conservation values (SCV) were found in embryonic-shifting or primary dune, while the lowest SCVs were found in driftline zone. There were significant differences among coastal dune zones regarding selected criteria.